Physiological and transcriptomic analysis of salt tolerant Glaux maritima grown under high saline condition - Gu, Rui; Wan, Zhi Qiang; Tang, Fang; Liu, Xue Ting; Yang, Yan ting; Shi, Feng ling (Frontiers in Plant Science, 2023)
Land salinization considerably limits crop production. Biological improvement of saline and alkaline land is an important way to achieve efficient land use. It is crucial to study the salt tolerance of halophyte resources in order to explore and improve plant resources through biological improvement. Glaux maritima is a mesophyte halophyte with strong salt tolerance. In this study, we investigated the mechanisms underlying the salt tolerance of G. maritima. Fixed paraffin sections, physiological and biochemical indices, and transcriptome of G. maritima leaves were analyzed under varied salt concentrations. Leaf cross-sections revealed that G. maritima has a salt gland tissue composed of stalk, collecting, and secretory cells, which are trapped in epidermal cells. At the physiological level, the maximum salt tolerance threshold of G. maritima leaves was 600 mM/L. At this concentration, proline content, relative conductivity, and superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) enzyme activities were maximum. At the transcriptional level, transcriptome data of three experimental groups (N0: 0 mM/L, N3: 600 mM/L, and N4: 800 mM/L) were analyzed, and six essential genes related to proline synthesis and five essential genes related to SOD and CAT enzyme activities were identified. Two genes involved in CAT enzyme activity were also found to play an important role in the MAPK signaling pathway. Trend analysis revealed that the MAPK signaling regulation (37 differentially expressed genes (DEGs)), phytohormone regulation (48 DEGs), glutathione metabolism (8 DEGs), flavonoid and flavonoid biosynthesis (2 DEGs), and flavonoid biosynthesis (24 DEGs) pathways played important roles in regulating the salt tolerance of G. maritima. These findings provide valuable information for further studies on the functional characteristics of G. maritima in response to abiotic stress and may contribute to salt resistance breeding of fodder crops for cultivation in saline alkali land.